Non-cognitive factors influencing science achievement in Malaysia and Japan: an analysis of TIMSS 2015 - Mohtar, Lilia Ellany; Halim, Lilia; Samsudin, Mohd. Ali; Ismail, Mohd Erfy (Modestum Publishing LTD, 2019)
Japan’s continual excellent achievement in TIMSS has led to many research and discussions of the Japanese school system as a way of understanding the factors and system that underlie Japan’s success in TIMSS. However, comparative studies have focused more on cognitive skills and less on non-cognitive skills as plausible factors for the continual success. Thus, this study aimed to examine the non-cognitive factors related to students’ science achievement in TIMSS. This study adopted secondary data analysis where the analysis was carried out on TIMSS 2015 data for respondents from Malaysia and Japan. This study proposed two models for each country which contained five constructs, namely four independent variables which are science teaching practices, victims of bullying, attitude towards science, school climate, and one independent variable i.e. science achievement. From the structural model of multiple group comparison analysis, almost all non-cognitive factors in the model showed significant difference between the two countries except for the relationship between attitude towards science and science achievement in TIMSS.